Analysis of the Impact of Gambling and Online Loans in the Perspective of Informatics, Islam, and Kemuhammadiyahan - Basri, Mhd.; Zulherry, Andi (-, 2025)
With the rapid development of digital technology, online lending services (pinjol) and online gambling (judol) have become more accessible. This raises significant concerns from the point of view of informatics, Islam, and Kemuhammadiyahan.  Using a descriptive quantitative method that combines informatics values, Islamic values, and Muhammadiyah socio-cultural principles, this study aims to analyze the influence of the two phenomena.  Data was collected through literature research and closed questionnaires distributed to one hundred respondents.  The results showed that the majority of people who participated in the study were of the opinion that pinjol and judol not only contradict Islamic principles but also support the use of sharia-based financial applications.  The research also emphasizes the importance of law enforcement and ethics when using technology. From an Islamic and Kemuhammadiyahan perspective, these two actions are considered haram and disrupt the harmony of society.  The solutions suggested by this research are improving education, improving technology ethics, and developing sharia-based financial services.